Agtrials - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Agtrials.org is an information portal developed by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) which provides access to a database on the performance of agricultural technologies at sites across the developing world. It builds on decades of evaluation trials, mostly of varieties, but includes any agricultural technology for developing world farmers. This project will standardize data and information to the benefit of climate change analyses, future multi-environment trials and research and development in international agriculture.